TINJAUAN POTENSI TEKNIS DAN KELAYAKAN EKONOMI PLTA PADA PROYEK KERJA SAMA PEMERINTAH DENGAN BADAN USAHA BENDUNGAN MERANGIN - Agustia Larasari; Jessica Sitorus; Moh. Bagus Wiratama Asad; Ary Firmana (JURNAL SUMBER DAYA AIR, 2021)
One of the utilizations of a multipurpose dam that has socio-economic value during its operation iselectricity generation. The addition of a hydropower component to a PPP project is quite a challenge due to substantial uncertainty related to hydrological aspects that will impact electricity production and revenue, as well as high initial investment costs for generating units. This study aims to map the technical potential of hydropower and evaluate the economic feasibility of hydropower in the Merangin Dam PPP Project. The potential for power and energy generation is obtained through simulations of the hydropower operation for 19 years using hydrological data, HEC-HMS model generated-data, and dam engineering design. According to the results, the technical potential of hydropower can produce, on average, power of Pp = 103.8 MW during peak load, Pb = 98.53 MW during base load, and total energy of 636.66 GWh/year. The economic potential is evaluated through social cost-benefits analysis (SCBA) by estimating the additional benefits obtained from the hydropower compared to the PPP structure of the Merangin Dam without hydropower. Through SCBA, the addition of hydropower to the Merangin Dam PPP structure has an EIRR value of 35.24%, NPV of Rp. 2.104.212.122.723,- and BCR = 3.06. Based on these indicators, the provision of hydropower plants is considered economically feasible because the benefits that will be generated and obtained by the community are higher than the economic costs incurred.Keywords: Technical potential, economic feasibility, hydropower plant, multipurpose dam, PPP